Stem cell-derived extracellular vesicles: A novel and potential remedy for primary ovarian insufficiency - Geng, Zixiang; Guo, Hailing; Li, Yifei; Liu, Ying; Zhao, Yongfang (Frontiers in Cell and Developmental Biology, 2023)
Primary ovarian insufficiency (POI) is an essential cause of young female fertility loss. At present, there are many treatments for primary ovarian insufficiency, but due to the complexity of the pathogenesis of primary ovarian insufficiency, the efficacy still could not be satisfactory. Stem cell transplantation is a feasible intervention protocol for primary ovarian insufficiency. However, its wide application in the clinic is limited by some defects such as tumorigenic and controversial ethical issues. Stem cell-derived extracellular vesicles (EVs) represent an important mode of intercellular communication attracting increasing interest. It is well documented that stem cell-derived extracellular vesicles for primary ovarian insufficiency with exciting therapeutic effects. Studies have found that stem cell-derived extracellular vesicles could improve ovarian reserve, increase the growth of follicles, reduce follicle atresia, and restore hormone levels of FSH and E2. Its mechanisms include inhibiting ovarian granulosa cells (GCs) apoptosis, reactive oxygen species, and inflammatory response and promoting granulosa cells proliferation and angiogenesis. Thus, stem cell-derived extracellular vesicles are a promising and potential method for primary ovarian insufficiency patients. However, stem cell-derived extracellular vesicles are still a long way from clinical translation. This review will provide an overview of the role and the mechanisms of stem cell-derived extracellular vesicles in primary ovarian insufficiency, and further elaborate on the current challenges. It may suggest new directions for future research.